Effects of Propolis on Storage of Sweet Cherry Cultivar Aksehir Napolyon - ERTURK CANDIR, ELIF; ERHAN OZDEMIR, AHMET; MINE SOYLU, EMINE; SAHINLER, NURAY; GUL, AZIZ (Asian Journal of Chemistry, 2010)
Sweet cherries cultivar Aksehir Napolyon were dipped in ethanol extracted propolis (EEP) and water extracted propolis (WEP) in various concentrations immediately after harvest and then kept at 0 ºC, 85-90 % relative humidity for 4 weeks. The following treatments were applied to the fruits: dipping in water, dipping in ethanol (70 %), dipping in 1, 5 and 10 % concentrations of ethanol extracted propolis and dipping in 1, 5 and 10 % concentrations of water extracted propolis. The effects of propolis on incidence of fungal decay and fruit quality (weight loss, total soluble solids, titratable acidity, skin colour, stem browning, surface pitting, appearance and taste) were assessed at weekly intervals during storage. Ethanol extracted propolis treatments were effective in preventing fungal decay in cherries for 4 weeks, but adversely affected sensory quality and stem colour of cherries.